2005
DOI: 10.1042/bse0410015
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligases

Abstract: The selectivity of the ubiquitin-26 S proteasome system (UPS) for a particular substrate protein relies on the interaction between a ubiquitin-conjugating enzyme (E2, of which a cell contains relatively few) and a ubiquitin-protein ligase (E3, of which there are possibly hundreds). Post-translational modifications of the protein substrate, such as phosphorylation or hydroxylation, are often required prior to its selection. In this way, the precise spatio-temporal targeting and degradation of a given substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
146
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(147 citation statements)
references
References 36 publications
1
146
0
Order By: Relevance
“…5,[8][9][10] Substrate recruitment in part occurs through ER-associated degradation, where misfolded protein is retro-translocated to the cytosol for proteasomal degradation. 11 Accumulation of misfolded proteins in the ER induces the UPR, resulting in a decreased rate of general transcription, whereas protein expression of selected chaperones (for example, GRP78/BiP, heat-shock proteins) is increased.…”
Section: Introductionmentioning
confidence: 99%
“…5,[8][9][10] Substrate recruitment in part occurs through ER-associated degradation, where misfolded protein is retro-translocated to the cytosol for proteasomal degradation. 11 Accumulation of misfolded proteins in the ER induces the UPR, resulting in a decreased rate of general transcription, whereas protein expression of selected chaperones (for example, GRP78/BiP, heat-shock proteins) is increased.…”
Section: Introductionmentioning
confidence: 99%
“…It is conjugated to more than 100 cellular proteins through the sequential action of three conjugation enzymes that are also induced by IFN-α/β: E1 (Ube1L) (2), E2 (UbcH8) (3,4), and E3 (Herc5) (5,6). The vast majority of IFN-induced ISG15 conjugation is mediated by a single E3 enzyme, Herc5, in contrast to the ubiquitin system that uses a large number of E3 enzymes to accomplish target selectivity (7).…”
mentioning
confidence: 99%
“…Recent studies have revealed that IKK activation by cytokines such as TNF and IL-1 and by Tolllike receptors is dependent on Lys63-linked nondegradative polyubiquitination (5). Using biochemical purification and in vitro reconstitution, it was shown that together with a ubiquitin activating enzyme (E1) and a specific dimeric ubiquitin conjugating enzyme Ubc13-Uev1A complex (E2), the RING domain containing protein TRAF6 acts as a specific ubiquitin ligase (E3) in this Lys63-linked polyubiquitination (6)(7)(8). A MAP kinase kinase kinase complex (MAP3K) known as the TAK1 complex containing the kinase TAK1 and two adapter proteins TAB1 and TAB2 is the intermediary in IKK activation.…”
mentioning
confidence: 99%